Human neuronal cell protein responses to Nipah virus infection - Chang, L.Y.; Ali, A.R.M.; Hassan, S.S.; AbuBakar, Sazaly (2007)
Background: Nipah virus (NiV), a recently discovered zoonotic virus infects and replicates in several human cell types. Its replication in human neuronal cells, however, is less efficient in comparison to other fully susceptible cells. In the present study, the SK-N-MC human neuronal cell protein response to NiV infection is examined using proteomic approaches. Results: Method for separation of the NiV-infected human neuronal cell proteins using two-dimensional polyacrylamide gel electrophoresis (2D-PAGE) was established. At least 800 protein spots were resolved of which seven were unique, six were significantly up-regulated and eight were significantly down-regulated. Six of these altered proteins were identified using mass spectrometry ( MS) and confirmed using MS/MS. The heterogenous nuclear ribonucleoprotein ( hnRNP) F, guanine nucleotide binding protein ( G protein), voltage-dependent anion channel 2 (VDAC2) and cytochrome bc1 were present in abundance in the NiV-infected SK-N-MC cells in contrast to hnRNPs H and H2 that were significantly down-regulated. Conclusion: Several human neuronal cell proteins that are differentially expressed following NiV infection are identified. The proteins are associated with various cellular functions and their abundance reflects their significance in the cytopathologic responses to the infection and the regulation of NiV replication. The potential importance of the ratio of hnRNP F, and hnRNPs H and H2 in regulation of NiV replication, the association of the mitochondrial protein with the cytopathologic responses to the infection and induction of apoptosis are highlighted.